The Study on Gelatine Addition to Acidity, pH, Water Holding Capacity and Syneresis of Yogurt (Faculty of Animal Science Universitas Brawijaya, 2008)
The objective of this study to find out the effect of gelatine addition as a stabilizer on acidity, pH, water holding capacity, and syneresis of yogurt. The material of these research were yogurt made from skim milk with 14% of total solid, yogurt starter which combination of Lactobacillus bulgaricus and Streptococcus thermophillus (1:1), and gelatine as a stabilizer. The method was experiment using Randomized Block Design, which the factor was the gelatine percentage (w/v) of 0 % (G0), 0.2% (G2), 0.4 % (G4), and 0.6 % (G6). The observed variables were syneresis, water holding capacity, acidity, and pH. Data was subjected to analysis of variance followed by Duncanâ€™s Multiple Range Test. The result of analysis variance showed that the addition of gelatine did not gave Â a significant effect (P>0.05) on acidity, significant effect (P<0.05) on pH and highly significant effect (P<0.01) on syneresis and water holding capacity of yogurt. It was concluded that the addition of gelatine as a stabilizer influences pH, water holding capacity and syneresis but gave no influence acidity of yogurt. The addition of 0,6% gelatine as a stabilizer could produce yogurt with low syneresis, high water holding capacity, and the normal pH. Keywords: Yogurt, gelatine, acidity, pH, water holding capacity, syneresis